KONEKSI POLITIK, KOMPENSASI EKSEKUTIF, FINANCIAL DISTRESS, KUALITAS AUDIT, DAN MANAJEMEN LABA : STUDI INDONESIA VS THAILAND - Apsari, A.A. Ayu Nur Cintya; Rasmini, Ni Ketut (Buletin Studi Ekonomi; VOLUME.28.NO.01.TAHUN.2023DO - 10.24843/BSE.2023.v28.i01.p03, 2023)
This study aims to obtain empirical evidence regarding the effect of political connections, executive compensation, and financial distress on earnings management with audit quality as a moderating variable in Indonesia and Thailand. This study took place in manufacturing companies listed on the Indonesia Stock Exchange (IDX) and The Stock Exchange of Thailand for the 2016-2020 period with a total sample of 60 samples in Indonesia and 65 samples in Thailand, which were taken using a purposive sampling method. This study uses panel data regression with the STATA application. The results show that political connections in Indonesia and Thailand, as well as executive compensation in Thailand have no effect on earnings management. Executive compensation in Indonesia, as well as financial distress in Indonesia and Thailand have a positive effect on earnings management. Audit quality can weaken the influence of political connections on management in Indonesia. Audit quality is not able to moderate political connections on earnings management in Thailand, executive compensation on earnings management in Indonesia and Thailand, and financial distress on earnings management in Indonesia and Thailand.